Under Stalin's shadow : a global history of Greek communism - Marantzidēs, Nikos A. (NIU series in Slavic, East European, and Eurasian studies., 2023)
"This book examines the history of the Communist party of Greece (KKE) between 1918 and 1956 from an international perspective. Because the frontiers between the national and the international in the Communist world were not so clearly separated, international Communist institutions, geopolitical soviet interests and sister parties' strategies shaped in fundamental ways the KKE's leadership, its character and decision-making mechanisms as a party, and the way of life of its followers"--